Determinants of consumer demand for circular economy products. A case for reuse and remanufacturing for sustainable development. (12th November 2020) - Hunka, Agnieszka D.; Linder, Marcus; Habibi, Shiva
Abstract: We investigate determinants of consumer demand for circular (reused and remanufactured) products. Based on exploratory choice‐based conjoint experiments with a sample of 800 adults in the United Kingdom, we examine two types of premium segment electronic appliances: a mobile phone and a robot vacuum cleaner. We find that consumers prefer partly circulated products over fully or not at all circulated products and that circular products can likely successfully enter the existing market at the retail price of a new product. Interestingly, circular products compete for market share primarily with new products, leaving the market share of second‐hand options less affected. The results show a promising path for firms considering a transition to circular business models.